2021
DOI: 10.1038/s42003-021-02309-5
|View full text |Cite
|
Sign up to set email alerts
|

TNF receptor agonists induce distinct receptor clusters to mediate differential agonistic activity

Abstract: Monoclonal antibodies (mAb) and natural ligands targeting costimulatory tumor necrosis factor receptors (TNFR) exhibit a wide range of agonistic activities and antitumor responses. The mechanisms underlying these differential agonistic activities remain poorly understood. Here, we employ a panel of experimental and clinically-relevant molecules targeting human CD40, 4-1BB and OX40 to examine this issue. Confocal and STORM microscopy reveal that strongly agonistic reagents induce clusters characterized by small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 82 publications
5
42
0
Order By: Relevance
“…In fact, in the PBMC assay, anti-hCD27 h1 treatment reduces CD8 + T-cell proliferation, suggesting possible depletion of CD27 + cells by NK cells in the culture. Further, enhanced clustering of CD27 by h2 compared to h1 mAb was observed in the absence of FcγR-expressing cells, supporting the ability of this isotype to cluster TNFR irrespective of FcγR binding and this is similar to OX40, 4-1BB and CD40 mAb 52 . Based on these findings, hCD27 h2, h1 V11 or SE/LF mAb deliver stronger agonism than h1 counterparts.…”
Section: Discussionmentioning
confidence: 52%
“…In fact, in the PBMC assay, anti-hCD27 h1 treatment reduces CD8 + T-cell proliferation, suggesting possible depletion of CD27 + cells by NK cells in the culture. Further, enhanced clustering of CD27 by h2 compared to h1 mAb was observed in the absence of FcγR-expressing cells, supporting the ability of this isotype to cluster TNFR irrespective of FcγR binding and this is similar to OX40, 4-1BB and CD40 mAb 52 . Based on these findings, hCD27 h2, h1 V11 or SE/LF mAb deliver stronger agonism than h1 counterparts.…”
Section: Discussionmentioning
confidence: 52%
“…67 Interactions of TNFA and TNFR1 leads to clustering of TRADD (TNF (Tumor Necrosis Factor) R1 (Receptor Type 1)-Associated Death Domain) results in activation of caspases leading to "Caspase Cascade" and apoptosis. 68,69 It is notable that the differential display in the expression of two (2) candidate genes, CASP9 and TNFRSF1A that were integral to these pathways were externally validated by quantitative RT-PCR experiments in the present study.…”
Section: Dovepressmentioning
confidence: 61%
“…Recent studies have shown that by simply switching the IgG isotypes (hIgG1→hIgG2), the CD40 antagonists can be converted into strong agonists, 54 possibly due to the hIgG2-mediated higher binding avidity and strong self-association tendency upon antigen binding. 55 Although such self-association has been previously described for other human IgG isotypes, 56 , 57 it is less likely that IBI37G5 exerts its agonistic activity through similar mechanism due to the much weaker self-association capability of hIgG1. In addition, the assembly of IgG1 oligomers is dependent on Fc-Fc interactions, 58 but the Fc-absent F(ab') 2 of IBI37G5 is fully functional, therefore excluding the effects of IgG self-assembly on agonist activity.…”
Section: Discussionmentioning
confidence: 91%